1984
DOI: 10.1038/307658a0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the mouse cellular Harvey-ras gene in chemically induced benign skin papillomas

Abstract: An important feature of the development of many human and animal tumours is the appearance of pre-malignant benign lesions, some of which undergo further changes during progression to malignancy. Many of the currently accepted concepts of multi-stage carcinogenesis have been developed using an experimental model based on the chemical induction of tumours in mouse skin. In this system, many of the premalignant papillomas which arise are promoter-dependent, and appear to regress if promoter treatment is interrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
245
3

Year Published

1984
1984
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 497 publications
(258 citation statements)
references
References 17 publications
8
245
3
Order By: Relevance
“…Moreover, recent transfection studies have revealed the presence of a distantly related N-ras oncogene (Hall et al, 1983 (Spandidos, 1983) the elevation observed here is not in itself sufficient to produce malignant change. Parallel studies in this laboratory, of carcinogen induced mouse skin papillomata, which have a similar potential for malignancy, have also demonstrated elevated Ha-ras oncogene expression and in addition, the DNA from these tumours has acquired transforming activity in transfection assays (Balmain et al, 1984). The cellular homologues of several retroviral oncogenes have been shown to exhibit tissuespecific patterns of transcriptional activity (Westin et al, 1982a,b, Gonda et al, 1982.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, recent transfection studies have revealed the presence of a distantly related N-ras oncogene (Hall et al, 1983 (Spandidos, 1983) the elevation observed here is not in itself sufficient to produce malignant change. Parallel studies in this laboratory, of carcinogen induced mouse skin papillomata, which have a similar potential for malignancy, have also demonstrated elevated Ha-ras oncogene expression and in addition, the DNA from these tumours has acquired transforming activity in transfection assays (Balmain et al, 1984). The cellular homologues of several retroviral oncogenes have been shown to exhibit tissuespecific patterns of transcriptional activity (Westin et al, 1982a,b, Gonda et al, 1982.…”
Section: Resultsmentioning
confidence: 97%
“…Our result indicates that in longterm TPA treated skin TGF-b signaling through the type II receptor is still possible. In the mouse skin carcinogenesis model over 90% of papillomas and carcinomas initiated by DMBA have a speci®c A?T transversion in the codon 61 of the Harvey-ras gene (Balmain et al, 1984;. This mutation is su cient to initiate skin in vivo, but secondary events are necessary to induce the development of tumors Bailleul et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…DMBA treatment of skin causes mutations at codon 61 of the ras gene leading to rasactivation (Balmain et al, 1984;Hennings et al, 1988) and FGF-BP expression is increased in DMBA/TPA induced papillomas and in cell lines MK ras , SP1 and 308 that carry an activated ras gene. In addition, FGF-BP mRNA levels are upregulated in mouse skin after application of the PKC-activator TPA alone.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that skin tumor initiation with DMBA causes an activating ras-mutation in codon 61 (Balmain et al, 1984). To test the hypothesis that ras activation plays a role for FGF-BP overexpression, we expressed activated ras in primary keratinocytes (MK ras ).…”
Section: Expression Of Fgf-bp During Skin Carcinogenesismentioning
confidence: 99%